SPE Annual Technical Conference and Exhibition 2012
DOI: 10.2118/159217-ms
|View full text |Cite
|
Sign up to set email alerts
|

Inclination Effects on Flow Characteristics of High Viscosity Oil/Gas Two-Phase Flow

Abstract: The effect of downward and upward pipe inclinations on flow characteristics for high viscosity oil-gas two-phase flow was experimentally studied. 400 experimental tests were conducted in a 50.8-mm ID pipe for ±2° inclinations. Four different oil viscosities, namely, 0.585, 0.378, 0.257 and 0.181 Pas, were considered. Superficial gas and liquid velocity varied from 0.1 to 3.5 m/s and 0.1 to 0.8 m/s, respectively. Flow pattern and pressure drop are reported. The experimental results were used to evaluate differe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
3

Relationship

5
4

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 16 publications
0
7
0
Order By: Relevance
“…All tests were conducted for horizontal flow and oil viscosities range from 0.121 Pa s to 1.0 Pa s. Kora (2010) conducted experiments and developed correlations for slug liquid holdup in horizontal high viscosity oil-gas flow. Jeyachandra (2011) studied the effect of the inclination angle for horizontal and nearhorizontal flow.…”
Section: Introductionmentioning
confidence: 99%
“…All tests were conducted for horizontal flow and oil viscosities range from 0.121 Pa s to 1.0 Pa s. Kora (2010) conducted experiments and developed correlations for slug liquid holdup in horizontal high viscosity oil-gas flow. Jeyachandra (2011) studied the effect of the inclination angle for horizontal and nearhorizontal flow.…”
Section: Introductionmentioning
confidence: 99%
“…Both Basha et al (2014), who worked with high inclinations and medium diameters, and Jeyachandra et al (2012), who worked with high viscosity oil, identified this same behavior concerning the inclination. However, apart from the single-phase flow, which presented a generally linear behavior, the relation between the pressure drop and the inclination could not be more quantitatively characterized.…”
Section: Pressure Drop and Pipe Wall Stressmentioning
confidence: 61%
“…Once the pipe is set, the second plug is released, which causes the fluid to drain and the bubble to enter the pipe and displace the liquid. The entrance of the bubble occurs due to gravitational potential energy generated from the hydrostatic pressure difference between the initial and final segment of the bubble nose [26]. The measuring procedure consisted of one calibrated chronometer set to start as soon as the upper end plug was released.…”
Section: Methodsmentioning
confidence: 99%